2006
DOI: 10.1002/ejic.200600174
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Sulfuration of the Terminal Phosphido Complex trans‐[PtCl(PHCy2)2(PCy2)]: Synthesis of [Pt(κ2S,S′‐PS2Cy2)(PHCy2)2]Cl and [Pt(κ2S,S′‐PS2Cy2){κP‐P(S)Cy2}(PHCy2)] and Crystal Structure of [Pt(κ2S,S‐PCy2S2)(κ‐S‐PCy2S2)(PHCy2)]

Abstract: The terminal phosphido complex trans‐[PtCl(PHCy2)2(PCy2)] (1) has been prepared, exploiting the reversibility of the reaction with HCl, by action of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) on [PtCl(PHCy2)3]Cl, and its reactivity towards elemental sulfur studied. The first product obtained by reaction of 1 with 1 equiv. of sulfur is trans‐[PtCl(PHCy2)2{κP‐P(S)Cy2}] (2), which rapidly isomerises in halogenated solvents into cis‐[PtCl(PHCy2)2{κP‐P(S)Cy2}] (3). Further addition of sulfur causes the formation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Deprotonation of [PtCl(PHCy 2 ) 3 ] + affords the dicyclohexylphosphanido complex trans ‐[PtCl(PHCy 2 ) 2 (PCy 2 )] ( 9 ), whose XRD structure is shown in Figure 1 27. Dynamic NMR spectroscopic studies revealed that 9 exhibits a dynamic process with an activation free energy (Δ G ‡ ) value of 34 kJ/mol 28.…”
Section: Terminal (Phosphanido)platinum Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Deprotonation of [PtCl(PHCy 2 ) 3 ] + affords the dicyclohexylphosphanido complex trans ‐[PtCl(PHCy 2 ) 2 (PCy 2 )] ( 9 ), whose XRD structure is shown in Figure 1 27. Dynamic NMR spectroscopic studies revealed that 9 exhibits a dynamic process with an activation free energy (Δ G ‡ ) value of 34 kJ/mol 28.…”
Section: Terminal (Phosphanido)platinum Complexesmentioning
confidence: 99%
“…The reactivity of the ancillary PHCy 2 ligands in 9 is shown in the sulfuration carried out with excess S 8 leading eventually to [Pt(κ 2 S , S′ ‐PCy 2 S 2 )(κ S ‐PCy 2 S 2 )(PHCy 2 )] ( 27 , Scheme ). Monitoring of the reaction showed that it proceeds stepwise, the first two S atoms attacking the terminal phosphanido P and further two S atoms attacking one of the bound PHCy 2 ligands 27…”
Section: Terminal (Phosphanido)platinum Complexesmentioning
confidence: 99%
“…10 Metal phosphanido complexes can also react directly with elemental selenium to give phosphinoselenoite and phosphinodiselenoate complexes. [11][12][13][14] Congruent with the reactivity at phosphorus, sulfur and selenium also oxidise germanium(II) complexes to form corresponding germanium(IV) chalcogenide complexes, [15][16][17][18][19][20] although analogous reactivity with tin or lead complexes is unknown. The oxidations are driven by the formation of strong P-E or Ge-E (E = S, Se) bonds; 21 however, competing reactivity of germanium and phosphorus centres with selenium has not been reported.…”
mentioning
confidence: 99%
“…This result is in contrast to previously reported oxidative reactivity between either germanium and selenium or phosphorus and selenium. [11][12][13][14][15][16][17][18][19][20] Compound 2 is the first structurally characterized example of a terminal -kSe bonding mode for the phosphinoselenoito anion, although a -kSe complex has been characterised spectroscopically. 24 The P-Se bond length [2.2602( 9) Å] is consistent with that of a single bond [2.26 Å], 12 suggesting localisation of charge on the chalcogen and a predominant contribution from the phosphinoselenoite [Cy 2 P-Se] À tautomer.…”
mentioning
confidence: 99%
“…The formation of P–S bond from coordinated diorganophosphanide and an S-based reactant is well-known. , Recently, a reversible intramolecular P–S bond formation/cleavage mediated by a Ni(0)/Ni­(II) system has been reported . However, to the best of our knowledge, all described cases result in complexes featuring a terminally bonded thiophosphane.…”
Section: Resultsmentioning
confidence: 99%